End-of-Life Decisions - Some International Comparisons - Michael M. Costello, Daniel J. West and Bernardo Ramirez (World Health & Population, 2014)
Healthcare professionals often confront difficult issues in end-of-life care. Caregivers who question futile care and treatment can find themselves at odds with patients, family members and surrogates who stress patient autonomy. Many developed nations recognize hospital ethics committees as appropriate venues for discussion of end-of-life care, and palliative care initiatives in many hospitals play important roles in patient care at the end of life. As health systems worldwide confront diminishing resources and endless questioning on expenditures, the concept of medical futility has taken on increasing prominence. Medical professionals know intuitively that certain interventions near the end of life can neither extend life nor improve the quality of life remaining. In addition to medical futility, concerns about international economic pressures and enhanced recognition of patient autonomy lead to questions as to the appropriateness of withdrawing life-sustaining treatment, assisted suicide and euthanasia. While some appellate courts seem willing to entertain questions on the legal rights of patients to access certain end-of-life measures, legislative bodies appear reluctant to legalize assisted suicide and euthanasia.
Keywords: end-of-life care, hospital ethics committees, end-of-life, assisted suicide, euthanasia